A Goldilocks Approach to Water Management: Hydrochannel Porous Transport Layers for Unitized Reversible Fuel Cells. Issue 16 (14th March 2023) - Komini Babu, Siddharth; Yilmaz, Abdurrahman; Uddin, Md Aman; LaManna, Jacob; Baltic, Eli; Jacobson, David L.; Pasaogullari, Ugur; Spendelow, Jacob S.
Abstract: This work presents a novel porous transport layer (PTL), the hydrochannel PTL, that enables improved water management and record high round trip efficiency in unitized reversible fuel cells (URFCs). URFCs require rapid transport of O2 and H2 O to provide high performance in both fuel cell and water electrolyzer operation, but cell design is complicated by conflicting water management requirements: electrolyzers perform best with high liquid water saturation, whereas fuel cells perform best when liquid water saturation is as low as possible while still maintaining effective ionomer hydration. The hydrochannel PTL circumvents this obstacle by providing hydrophilic channels for water transport through an otherwise hydrophobic PTL, enabling optimal performance in both fuel cell and water electrolyzer modes. Neutron radiography measurements of water content in both operating modes confirm that the hydrochannel PTL enables high performance due to its improved water management capabilities. Abstract : Unitized reversible fuel cells operate in both water electrolyzer (WE) and fuel cell (FC) mode for energy storage and generation, respectively. This work resolves the conflicting wettability requirements, for optimal performance in both WE and FC mode, through design of a novel hydrochannel porous transport layer, in which liquid and gas transport are partitioned into discrete hydrophilic and hydrophobic channels.